THE EFFECTS OF WORK DISCIPLINE, WORK LOYALTY, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE IN THE REGIONAL TAX DIVISION I AT THE REGIONAL REVENUE AGENCY OFFICE OF BATAM CITY - Saputra, Tengku Izan; Sabri, Sabri; Sumardin, Sumardin (Yayasan Education and Social Center, 2025)
This study aims to analyze the influence of work discipline, work loyalty, and work motivation on the performance of Regional Tax I employees at the Batam City Regional Revenue Agency Office. The study used a quantitative, census-based approach, with the entire population of 81 employees serving as respondents. Data were collected through a questionnaire that had been tested for validity and reliability. The test results showed that all statement items were valid (r > 0.218, p < 0.05) and reliable (Cronbach's Alpha > 0.60). Data analysis was conducted using multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The results of the study indicate that partial work discipline has a positive and significant effect on employee performance; work loyalty also has a positive and significant effect, and work motivation has a positive and significant effect, with the latter being the most dominant contributor. Simultaneously, work discipline, work loyalty, and work motivation have a significant effect on employee performance. The coefficient of determination of 0.719 indicates that 71.9% of the variation in employee performance is explained by the three independent variables, with the remaining 28.1% attributed to other factors outside the study. This finding emphasizes the importance of integrated human resource management in improving the performance of public sector employees.